Avaliação biomecânica da marcha com exoesqueleto robótico em sujeitos com AVC crônico - Lima, Jéssica Paola Souza (2018)
Objective: To evaluate the effect of the use of a left knee robotic exoskeleton on the kinetics and kinematics of patients with neuromotor dysfunction due to stroke. Methodology: Angular (inertial) and electromyographic (sEMG) biomechanical standards were compared during free running and with the robotic exoskeleton developed at UFES, in a 10 meter course. Previously, there was the evaluation of the Maximum Voluntary Contraction (MCV) of the muscles Erector spinae, Semitendinosus, and Rectus femoris for the normalization of the data. Results: Two subjects with chronic stroke participated in the experiments, and in one subject a correlation coefficient of agreement (pc)> 0.80 was detected in the angular patterns of right knee flexion and right hip flexion, and another subject was detected a moderate correlation in the angular pattern (pc> 0.80) of hip flexion. Pearson correlation coefficient (r) <0.5 was found in trunk flexion and planti / dorsiflexion of the left ankle of the first subject and in the values of trunk lateralization and flexion / extension of the left knee of the second subject. In the first subject, an accuracy of 70% was found in hip flexion, right knee flexion, and planti / dorsiflexion, while the second subject showed Cb <70% only in the lateralization angles of the trunk and flexion / extension of the left knee. The first subject presented a statistically significant difference (p> 0.05) in muscle activation peaks. Conclusions: The results regarding the biomechanical analysis of people with chronic stroke were satisfactory. There is a need for the implementation of the experimental protocol in a greater number of subjects with stroke or other neuromotor complications.